Pengaruh Manajemen Modal Kerja terhadap Profitabilitas Perusahaan - Lindananty; Nursahira, Meirina (JOURNAL AKSES STIA MALANG, 2025)
Abstract This study aims to examine the effect of working capital management on firm profitability. Working capital management is measured by five indicators: inventory conversion period, receivables conversion period, payables conversion period, cash conversion cycle, and cash conversion efficiency. Profitability is assessed using four ratios: Net Profit Margin (NPM), Return on Asset (ROA), Return on Equity (ROE), and Return on Capital Employed (ROCE). This is a quantitative research using secondary data from the financial statements of 24 food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the period 2019–2021. The regression analysis results indicate that all working capital indicators significantly and positively affect all four profitability measures. The efficiency of receivables and cash management contributes most dominantly to increasing profitability. These findings reinforce the importance of working capital management in supporting short-term financial performance and achieving corporate profitability. Keywords: cash efficiency; profitability; return on asset; return on equity; working capital management.